KEDUDUKAN HUKUM PUTUSAN PENGADILAN TERHADAP PENYELESAIAN PERSELISIHAN PERJANJIAN YANG TERDAPAT KLAUSULA ARBITRASE (Studi Putusan Mahkamah Agung Nomor 17 B/Pdt.Sus-Arbt/2014) - Nisan Rolan Wijaya, (2021)
Arbitration has absolute authority by the Arbitration Law to be able to examine or adjudicate disputes outside the court, which arise from disputes between the parties due to an agreement with an arbitration clause in it, which is limited by its authority in trade disputes. The District Court is given the authority by the Arbitration Law to handle disputes where the agreement contains an arbitration clause and legal consequences in deciding a dispute over an agreement with an arbitration clause. The use of this research methodology is normative legal research. The results of this study, first, the arbitration authority in the settlement of disputes in an agreement that contains an arbitration clause, in which in this study the arbitration has no authority in disputes because it is not a trade dispute. Second, the legal standing of the court's decision on the settlement of agreement disputes contained in an arbitration clause, where the Supreme Court in its decision number 17 B / Pdt.Sus-Arbt / 2014 dated 29 October 2014, according to the court is the authority of Industrial Relations Disputes. The formulation of the arbitration clause in the agreement should be made comprehensively and clearly in order to avoid obstacles in the implementation of arbitration in the future and to understand the limitations of arbitration authority and court authority in the agreement with arbitration clause. Keywords: Arbitration, Courts, Arbitration Clauses